2017
DOI: 10.1007/s00276-017-1885-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound visualization of an underestimated structure: the bicipital aponeurosis

Abstract: PurposeWe established a detailed sonographic approach to the bicipital aponeurosis (BA), because different pathologies of this, sometimes underestimated, structure are associated with vascular, neural and muscular lesions; emphasizing its further implementation in routine clinical examinations.MethodsThe BA of 100 volunteers, in sitting position with the elbow lying on a suitable table, was investigated. Patients were aged between 18 and 28 with no history of distal biceps injury. Examination was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The graded compression technique was applied to move the transducer slowly over the muscles. The authors of other studies also used this method for the identification of individual muscles [43,44] as this technique visualises muscles better than others. In addition, US also enables the analysis of fascial structures [45].…”
Section: Discussionmentioning
confidence: 99%
“…The graded compression technique was applied to move the transducer slowly over the muscles. The authors of other studies also used this method for the identification of individual muscles [43,44] as this technique visualises muscles better than others. In addition, US also enables the analysis of fascial structures [45].…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques provide details about the extension of the rupture to a single head (short‐ or long‐head rupture) and extension to the lacertus fibrosus as well as evaluate the degree of tendon retraction (Figures and ) . Retraction of the belly muscle usually occurs when the lacertus fibrosus is torn or partial rupture of the long head has occurred, and it does not occur when only the short head is torn, probably because the latter is contiguous with the lacertus fibrosus . In addition, US enables one to differentiate between full and partial tears via posterior acoustic shadowing, which is present in 97% of full tears.…”
Section: Ruptured Dbbt: Pathophysiologic Mechanisms and Imaging Appeamentioning
confidence: 99%
“…23 Retraction of the belly muscle usually occurs when the lacertus fibrosus is torn or partial rupture of the long head has occurred, and it does not occur when only the short head is torn, probably because the latter is contiguous with the lacertus fibrosus. 15,24 In addition, US enables one to differentiate between full and partial tears via posterior acoustic shadowing, which is present in 97% of full tears. However, an absence of shadowing does not effectively exclude the possibility of a partial tear.…”
Section: Ruptured Dbbt: Pathophysiologic Mechanisms and Imaging Appeamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in vitro has been reported that passive tension of the medial forearm musculature increases elbow stability when the forearm is supinated (Seiber et al, 2009). Certain researchers, including Konschake et al and Snoeck et al, have proposed that different structures, such as biceps brachii muscle (biceps) and antebrachial fascia, may be related to changes in the stiffness of the medial forearm muscle (Konschake et al, 2017; Snoeck, 2021; Snoeck et al, 2014). The biceps as supinator may increase the passive tension of the medial forearm musculature through the antebrachial fascia (Konschake et al, 2017, Snoeck, 2021, Snoeck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%